Non‐leukemic pediatric mixed phenotype acute leukemia/lymphoma: Genomic characterization and clinical outcome in a prospective trial for pediatric lymphoblastic lymphoma. Issue 6 (21st January 2019) - Martin‐Guerrero, Idoia; Salaverria, Itziar; Burkhardt, Birgit; Chassagne‐Clement, Catherine; Szczepanowski, Monika; Bens, Susanne; Klapper, Wolfram; Zimmermann, Martin; Kabickova, Edita; Bertrand, Yves; Reiter, Alfred; Siebert, Reiner; et al.
Abstract: Rare cases of hematological precursor neoplasms fulfill the diagnostic criteria of mixed phenotype acute leukemia (MPAL), characterized by expression patterns of at least two hematopoietic lineages, for which a highly aggressive behavior was reported. We present a series of 11 pediatric non‐leukemic MPAL identified among 146 precursor lymphoblastic lymphomas included in the prospective trial Euro‐LBL 02. Paraffin‐embedded biopsies of 10 cases were suitable for molecular analyses using OncoScan assay ( n = 7), fluorescence in situ hybridization (FISH; n = 7) or both ( n = 5). Except for one case with biallelic KMT2A (MLL) breaks, all cases analyzed by FISH lacked the most common translocations defining molecular subsets of lymphoblastic leukemia/lymphomas. Two non‐leukemic B‐myeloid MPALs showed the typical genomic profile of hyperdiploid precursor B‐cell lymphoblastic leukemia with gains of chromosomes 4, 6, 10, 14, 18, and 21. One B‐T MPAL showed typical aberrations of T‐cell lymphoblastic lymphoma, such as copy number neutral loss of heterozygosity (CNN‐LOH) at 9p targeting a 9p21.3 deletion of CDKN2A and 11q12.2‐qter affecting the ATM gene. ATM was also mutated in a T‐myeloid MPAL case with additional loss at 7q21.2‐q36.3 and mutation of NRAS, two alterations common in myeloid disorders. No recurrent regions of CNN‐LOH were observed. The outcome under treatment was good with all patients being alive in first complete remission after treatment according to a protocol for precursor lymphoblastic lymphoma (follow‐up 3‐10 years, median: 4.9 years). In summary, the present series of non‐leukemic MPALs widely lacked recurrently reported translocations in lymphoid/myeloid neoplasias and showed heterogeneous spectrum of chromosomal imbalances.